Association between migraine and Alzheimer’s disease: a nationwide cohort study - Kim, Jaeho; Ha, Woo Seok; Park, Sang Hyun; Han, Kyungdo; Baek, Min Seok (Frontiers in Aging Neuroscience, 2023)
Background and objective Migraine is a common chronic neurological disease characterized by pulsating headaches, photophobia, phonophobia, nausea, and vomiting. The prevalence of dementia in individuals aged over 65 years in Korea is more than 10%, and Alzheimer’s disease (AD) dementia accounts for most cases. Although these two neurological diseases account for a large portion of the medical burden in Korea, few studies have examined the relationship between the two diseases. Therefore, this study investigated the incidence and risk of AD in patients with migraines. Methods We retrospectively collected nationwide data from a national health insurance claims database governed by Korea’s National Health Insurance Service. Among Koreans in the 2009 record, patients with migraine were identified according to the International Classification of Diseases, 10th revision (ICD-10) code G43. First, we screened the database for participants aged over 40 years. Individuals diagnosed with migraine at least twice over more than 3 months in a year were considered to have chronic migraine in this study. Further, all participants with an AD diagnosis (ICD-10 code: Alzheimer’s disease F00, G30) were investigated for AD dementia development. The primary endpoint was AD development. Results The overall incidence of AD dementia was higher in individuals with a history of migraine than in those with no migraine history (8.0 per 1,000 person-years vs. 4.1 per 1,000 person-years). The risk of AD dementia was higher in individuals diagnosed with migraine (hazard ratio = 1.37 [95% confidence interval, 1.35–1.39]) than in the control group after adjustments for age and sex. Individuals with chronic migraine had a higher incidence of AD dementia than those with episodic migraine. Younger age (<65 years old) was associated with an increased risk of AD dementia compared to older age (≥65 years old). Higher body mass index (BMI) (≥25 kg/m2) was also associated with an increased risk of AD dementia compared to lower BMI (<25 kg/m2) (p < 0.001). Conclusion Our results suggest that individuals with a migraine history are more susceptible to AD than those without a migraine history. Additionally, these associations were more significant in younger and obese individuals with migraine than in individuals without migraine.